Catalytic bioscavengers in nerve agent poisoning: A promising approach?. (26th February 2016) - Worek, Franz; Thiermann, Horst; Wille, Timo
Highlights: Catalytic bioscavengers are considered promising for treatment of nerve agent poisoning. Recent in vitro and in vivo data support the bioscavenger concept. Catalytic bioscavengers are substrate specific and do not cover the spectrum of threat agents. The biological stability of catalytic bioscavengers is inadequate and needs substantial improvement. Further research is needed to transfer catalytic bioscavengers into advanced development and human use. Abstract: The repeated use of the nerve agent sarin against civilians in Syria in 2013 emphasizes the continuing threat by chemical warfare agents. Multiple studies demonstrated a limited efficacy of standard atropine–oxime treatment in nerve agent poisoning and called for the development of alternative and more effective treatment strategies. A novel approach is the use of stoichiometric or catalytic bioscavengers for detoxification of nerve agents in the systemic circulation prior to distribution into target tissues. Recent progress in the design of enzyme mutants with reversed stereo selectivity resulting in improved catalytic activity and their use in in vivo studies supports the concept of catalytic bioscavengers. Yet, further research is necessary to improve the catalytic activity, substrate spectrum and in vivo biological stability of enzyme mutants. The pros and cons of catalytic bioscavengers will be discussed in detail and future requirements for the development of catalytic bioscavengers will be proposed.